L'accompagnement des stages en formation initiale des enseignant·e·s du primaire en RDC - Joséphine Zihalirwa; Mariane Frenay; Denis Bédard
Instructional supervision practices adopted by teams providing internship support depend on how the support is perceived and the context in which the internship takes place. These practices have been tested in a Western context. However, in the Democratic Republic of Congo (DRC), the context of the initial training of primary school teachers raises questions about the possibility of transferring instructional supervision practices as they are. This article presents a study conducted in twenty primary and secondary schools. The study reports on how the process of supporting trainee teachers was modelled based on field data. Our data come from a field survey conducted through semi-structured interviews, focus groups and participant observation. The participants observed the support models of experienced trainee teachers in western countries. This modelling is the starting point of a reflexive approach to develop and implement new instructional supervision practices.